The developmental toxicity of bisphenol F exposure on the zebrafish larvae - Biyu Wu; Zirui Cheng; Xiang Li; Minxing Liang; Xue Wang; Duan Pi; Jiayi Liu; Huiling Li; Jun Zhao; Junjie Wang; Fang Liang; Xuegeng Wang (Ecotoxicology and Environmental Safety)
As a major substitute for the bisphenol A (BPA), the use of the bisphenol F (BPF) has increased dramatically in recent years. Growing evidence suggest that BPF shares numerous toxicological properties with BPA, raising the concerns about its potential impact on the health of organisms. However, the developmental toxicity of BPF remains poorly understood. In this study, we conducted a 5-day BPF exposure experiment on zebrafish (Danio rerio) from blastula stage at concentrations of 2, 20, 200, and 2000 µg/L. Our results demonstrated a significant increase in hatching rates across all treatment groups at 2 days post-fertilization (dpf). The esr1 was significantly upregulated at 2000 µg/L by 5 dpf, while no significant change was observed in ar. The frequency of operculum loss significantly increased at exposure concentrations of 20, 200, and 2000 µg/L, and a notable increase in notochord loss was observed at 2000 µg/L. To explore the underlying mechanisms, transcriptomic analysis was performed to identify differentially expressed genes (DEGs). GO and KEGG pathway enrichment analysis revealed that the toxic effects of BPF were closely associated with osteoclast differentiation, the FoxO signaling pathway, and the MAPK signaling pathway. These pathways influenced critical biological processes, including response to stimuli, animal organ morphogenesis, detoxification, and biomineralization. This study provides evidence that BPF exposure at environmentally relevant concentrations (2 µg/L) is harmful to hatching, concentrations above 20 µg/L exhibit estrogenic-disrupting activity and exert toxicological effects on the development of the head skeleton in zebrafish. These effects are particularly linked to disruptions in osteoclast differentiation.